Oblivious Transfer Based on the McEliece Assumptions with Unconditional Security for the Sender - David, Bernardo M.; Nascimento, Anderson C. A.; Nogueira, Rodrigo B. (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg), 2010)
In this paper we propose the first code-based oblivious transfer protocol with perfect (unconditional) security for one of the parties. To obtain this result we show that the McEliece cryptosystem is rerandomizable, a property that might be of independent interest.